PESTICIDES: Advances in Chemical and Botanical Pesticides - R.P. Sundararajan , ed; R.P. Sundararajan , ed (Croatia INTECH, 2012)
This book volume comprises of three different sections of which first section is on pesticide toxicity with seven chapters.
Pesticide Toxicity Botanical Pesticides Pest Management
Keywords: Pesticide Toxicity; Botanical Pesticides; Pest Management